Paradigma Komunikasi Pemimpin Bambu Muda Untuk Mencapai Kesusksesan - Siti Zaenab (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2019)
The purpose of leadership is to get trust in carrying out organizational tasks and taking fresh decisions so that the organization can run well. Besides, the leader in communicating with subordinates in hopes of approaching members of subordinator. To implement the approach is based on the paradigm of young bamboo leaders. Conclusions of the results of the research are found in the paradigm of young bamboo leaders where a leader can approach or relate to subordinates by way of attitudes and actions that force subordinates to occupy positions that do not have the competencies and qualifications that are appropriate to the needs so that what they want is not met with rules. The pa radigm of the young bamboo leader is; 1) truth is a state of relative nature. In general the truth is a situation and situation that does not harm any party and can please and delight all parties. But the current conditions turned upside down. 2) Heart sanctity is an attitude of calm that is calm in carrying out leadership tasks that are difficult to be influenced by negative elements such as selfishness, always acting based on rules and applicable laws. But now it is inversely proportional to doing arbitrariness or arrogant leadership towards subordinates. (3) Beauty is something that can be seen by the naked eyes. But instead leadership feels jealous and envious of subordinates who can be seen in plain view.